Three dimensional pelvis and hip interaction during punt kicking: Skilled versus novice players - Sayers, M.; Morris, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to examine the interrelationships between pelvis and hip kinematics and punt kicking proficiency during a series of kicks for maximum distance/velocity. Three dimensional data (500 Hz) were collected during punt kicks for maximum velocity performed by 15 semi professional (S-Pro) Rugby Union players and 15 male recreational (Rec) kicking sport athletes. Results showed that the punt kicking technique of the S-Pro group involved complex multiplanar pelvis movements, with greater emphasis on axial pelvis rotation than the Rec group. These movement patterns have the potential to increase the stretch-shorten cycle in the kicking leg. Conversely, the punt kicking technique of the Rec group involved simple flexion-extension pelvis and hip movement patterns, a strategy that appears to limit punt kicking ball velocity.